2018
DOI: 10.1097/md.0000000000010160
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma interacted with BDNF Val66Met influence schizophrenic symptoms

Abstract: The gene – environment (G × E) interaction effect is involved in severe mental disorders. However, whether the brain-derived neurotrophic factor (BDNF) Val66Met polymorphism participates in the childhood-abuse influenced schizophrenic symptoms remains unclear. We examined the interaction between BDNF Val66Met, and childhood trauma (ChT) on psychotic symptoms in a Chinese Han population.To estimate the G × E interaction, psychiatric interviews, self-report questionnaires for ChT, and genotyping for BDNF Val66Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…ChT is probably the most important environmental factor associated with SCZ [ 20 ]. There is evidence of multiple paths between traumatic experiences and psychosis.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…ChT is probably the most important environmental factor associated with SCZ [ 20 ]. There is evidence of multiple paths between traumatic experiences and psychosis.…”
Section: Reviewmentioning
confidence: 99%
“…Research has also shown that the genetic factor brain-derived neurotrophic factor (BDNF) Val66Met polymorphism directly connects to SCZ symptoms, in addition to the interplay of genes and environmental factors, especially ChT. When exposed to ChT, BDNF Met carriers have increased positive psychotic experiences compared to their counterparts [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…56 Although we do not wish to over interpret our results, we will have not yet been validated in the literature also show involvement in the pathogenesis of neurodevelopmental disorders (SLC9A6, 84,85 PPP1R15B 86 are associated with intellectual disability 87 ). 95 Overall, our findings indicate that changes in miRNA expression driven by in utero opioid exposure could play an important role in regulating the expression of genes associated with developmental disorders and psychiatric diseases during critical stages of embryonic development. BDNF is a validated target of miR 10b-5p 88 and miR10a-5p 89,90 that is involved in the pathogenesis of alcohol abuse, 89,91 opioid use 92,93 and cocaine use, 94 Huntington's disease 88 and schizophrenia.…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 63%
“…BDNF is a validated target of miR 10b-5p 88 and miR10a-5p 89,90 that is involved in the pathogenesis of alcohol abuse, 89,91 opioid use 92,93 and cocaine use, 94 Huntington's disease 88 and schizophrenia. 95 Overall, our findings indicate that changes in miRNA expression driven by in utero opioid exposure could play an important role in regulating the expression of genes associated with developmental disorders and psychiatric diseases during critical stages of embryonic development.…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 63%
“…The onset age of SZ is early and the disease has a chronic progression (3). Progressive aggravation or deterioration, accompanied by social dysfunction along with high disability rate and death rate can create a great burden to the society (4). At present, the pathogenesis of SZ is unclear, however results obtained from prior studies have revealed that genetic factors play an important role in the pathogenesis of SZ (5,6).…”
Section: Introductionmentioning
confidence: 99%